2007
DOI: 10.1128/mcb.00068-07
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Focal Adhesion Kinase Leads to Defects in Ventricular Septation and Outflow Tract Alignment

Abstract: To examine a role for focal adhesion kinase (FAK) in cardiac morphogenesis, we generated a line of mice with a conditional deletion of FAK in nkx2-5-expressing cells (herein termed FAK nk mice). FAK nk mice died shortly after birth, likely resulting from a profound subaortic ventricular septal defect and associated malalignment of the outflow tract. Additional less penetrant phenotypes included persistent truncus arteriosus and thickened valve leaflets. Thus, conditional inactivation of FAK in nkx2-5-expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 81 publications
3
49
1
Order By: Relevance
“…FAK activation occurring 24 h after TGFβ challenging in MVEC 18 is consistent with previous data [39]. Levels of FAK protein expression and/or activation have been correlated to phenotypic changes that affect cell differentiation and function, notably adhesion and migration, in a number of tissues [40][41][42][43]. Targeted FAK deletion in vascular endothelial cells leads to apoptosis and aberrant cell movement whereas FAK overexpression results in increased angiogenesis [44,45].…”
Section: Discussionsupporting
confidence: 88%
“…FAK activation occurring 24 h after TGFβ challenging in MVEC 18 is consistent with previous data [39]. Levels of FAK protein expression and/or activation have been correlated to phenotypic changes that affect cell differentiation and function, notably adhesion and migration, in a number of tissues [40][41][42][43]. Targeted FAK deletion in vascular endothelial cells leads to apoptosis and aberrant cell movement whereas FAK overexpression results in increased angiogenesis [44,45].…”
Section: Discussionsupporting
confidence: 88%
“…Focal adhesions are essential for maintaining structural integrity of vessels by inducing cytoskeletal rearrangements and alignment of vSMCs in response to mechanical strain. Previous studies have shown that genetic deletion of FAK (Ptk2) in vSMC precursors leads to defects in the patterning of the aortic arch arteries and septation of the heart and outflow tract (Hakim et al, 2007;Vallejo-Illarramendi et al, 2009;Cheng et al, 2011). These defects, however, are caused by abnormal recruitment (Hakim et al, 2007;Cheng et al, 2011) and/or impaired differentiation of vSMCs (Vallejo-Illarramendi et al, 2009), neither of which was seen in our mutants.…”
Section: Role Of α5 and αV Integrins In Cardiovascular Developmentcontrasting
confidence: 48%
“…Nkx2.5Cre is active in ventricular and atrial myocardium and also in the endocardium and epicardium, and achieves very high efficiency recombination (see Fig. S8 in the supplementary material); several previous studies have confirmed that Nkx2.5Cre and certain other Cre drivers cause more severe heart phenotypes than does MLC2vCre when crossed to the same target genes (Shai et al, 2002;Hakim et al, 2007;Peng et al, 2008;Ieda et al, 2009).…”
Section: A Developmental Heart Phenotype In Igf Receptor Mutantsmentioning
confidence: 95%